A Study on Social Support and Level of Depression among Alcohol Addicts” With Special Reference to Coimbatore Districts (International Journal of Scientific Research and Management (IJSRM), 2022)
Alcoholism is a major problem in India, and there is a large body of literature in India and the West devoted to understanding the marital dynamics involved in drinking and determining the negative effects that alcoholism can have on a spouse’s personality and function. Alcoholism is a condition that develops over time and is frequently fatal. It is not a symptom of another sickness or emotional issue, but rather a distinct ailment. A person’s size, weight, age, and sex, as well as the amount of food and alcohol ingested, all influence the effects of alcohol use. Even at low doses, alcohol can impair judgement and coordination dramatically. Alcohol in small to moderate dosages can potentially raise the risk of cancer. Low to moderate amounts of alcohol can enhance the likelihood of a number of aggressive behaviours, such as domestic violence and child abuse. Alcohol has a negative impact on not just an individual’s physical health, but also on the people around him. Alcoholism is linked to a shattered family role, a breakdown in family communication, as well as physical and mental disorders. Methodology of Study: The current study used a descriptive research design and probability sampling as the sampling method. To obtain data from parents for this study, the researcher used a basic random sampling lottery procedure. An interview schedule was used to acquire a sample size of 60 people.